The garden as Raumkunstwerk: the role of early 20th-century architecture schools for the modernisation of landscape architecture education - Lars Hopstock (Projets de Paysage)
The process leading to the first full academic curriculum for the discipline of landscape architecture in Germany being introduced in 1930 is relatively well-researched. Until then, garden design had been taught at special horticultural institutes. However, in the course of reform processes during the early 20th century, the subject of the garden was also introduced in different form and at different types of institutions of higher education as connected to architecture. This correlated with two subfields: architectural design and urban planning theory. The present paper’s first aim is to give a first overview over the variety of partly little-known curricula and courses that addressed open space design, respectively the personalities involved. By referring to a wide scope of sources, connections are disclosed between academia and some of the theoretical works addressing the garden. Within the profession of landscape architecture all the new educational options were known, which leads to the assumption that these options represented a source of inspiration for reforming landscape architecture education in the early 20th century.